Preliminary validation of the short physical performance battery in older adults with multiple sclerosis: secondary data analysis - Motl, Robert W. (BMC Geriatr, 2015)
BACKGROUND: There are relatively few standard, objective measures for studying physical function among older adults with multiple sclerosis (MS), yet such measures are necessary considering the shift in prevalence and associated consequences of both MS and older age on physical function. We undertook a preliminary examination of the construct validity of Short Physical Performance Battery (SPPB) scores in older adults with MS based on an expected differential pattern of associations with measures of lower and upper extremity function. METHODS: The sample included 48 persons with MS aged 50 years and older who were enrolled in a pilot, randomized controlled trial of exercise training. Participants completed the SPPB and other objective and self-report measures of lower and upper extremity function as part of baseline testing. RESULTS: SPPB scores demonstrated strong associations with measures of lower extremity function (|r(s)| = .66–.79), and weak associations with measures of upper extremity function (|r(s)| = .03–.33). CONCLUSIONS: We provide preliminary evidence that supports the validity of scores from the SPPB as a measure of lower extremity function for inclusion in clinical research and practice involving older adults with MS.